Potentialities and limits of short supply-chains - Belletti, G.; Marescotti, A. (Progress in Nutrition, 2013)
In recent years, short supply-chains initiatives show a growing diffusion, proposing themselves as an alternative to long supply-chains, dominated by firms and institutions accused of imposing on farmers and consumers production models with negative effects on economy, society, environment, nutrition. Indeed, the word "short supply-chain" encompasses a wide range of different initiatives and operational models that suggest caution in operating this type of comparison and evaluation. The aim of this work is to provide a key to the analysis of the potentialities and limits of short supply-chains based on three critical dimensions: logistics, information transmission, and distribution of the economic value. Basing on the analysis of two case-studies (“fair price” in farmers' markets in Tuscany, and the marketing of the meat of native breeds in the province of Grosseto), the paper shows that not always short supply-chain initiatives can compete with the long chains as regards the achievement of a greater compression of production and distribution costs. However, the evaluation should be made primarily on the basis of ability short supply-chains initiatives have to achieving the goals that operators have set. In this sense, some initiatives of short supply-chain show higher potential than the long chain.